Real-time heat input monitoring towards robust GMA brazing. (2nd January 2019) - Makwana, Pinaac; Goecke, Sven-F; De, Amitava
ABSTRACT: Gas metal arc (GMA) brazing of thin sheets requires active control of heat input, filler alloy deposition and temperature field on sheet surface. A novel attempt is presented here for a rapid synchronous real-time monitoring of current and voltage transients, filler alloy depositions and temperature field using, respectively, a high-frequency recorder, high-speed videography and two thermal infrared cameras during GMA brazing of galvanized steel sheets. For heat inputs from 100 to 200 J mm −1, the peak temperature varied from 1500 to 1700 K. The high-speed videography showed consistent filler deposition and bead profile. The methodology and results presented here depict a promising resource for real-time monitoring and feedback control of GMA brazing.